Anemia and Mineral Bone Disorders in Patients with End Stage Renal Disease on Maintenance Hemodialysis - Anees, Muhammad; Ahmad, Sajjad; Raja, Khalid Mahmood; Mushtaq, Mirrah; Ibrahim, Muhammad (Pakistan Journal of Kidney Diseases, 2021)
Objective: To observe the pattern of anemia and mineral bone disorders (MBD)in patients with End Stage Renal Disease (ESRD) on maintenance hemodialysis (MHD) at Nephrology Department, Mayo Hospital and Shalamar Hospital, Lahore. Methodology: Two hundred patients who were undergoing MHD for more than three months were included in the study. Patients with Acute Kidney Injury (AKI) were excluded from the study. Patient’s demographic data, laboratory reports and dialysis record were noted in a predesigned proforma. Results: Two hundred patients were included in study, 105(52.5%) were male and rest of them were female. Major cause of ESRD was Diabetes Mellitus 83 (41.5%) followed by Hypertension 80 (40%) and Nephrolithiasis 15 (7.5%). Most of the patients belonged to middle age group, poor socioeconomic class, lower level of education and were getting twice-weekly dialysis. Mean hemoglobin was 10.17±1.69 gm/L and most of the patients 137 (68.5%) were anemic with hemoglobin level less than 11gm/dl. Iron was adequate in 170 (85%) patients with transferrin saturation more than 20%. Hypocalcemia (<8.5mg/dl), hypophosphatemia and calcium phosphorus product was less than 55 in 138(69%), 42(21%), 175(87.5%) respectively. Intact PTH was less than 100 pg/ml in 16(8.0%) patients supporting adynamic bone disease according to KDOQI guidelines and rest of the patients 184(92%) were having Intact PTH more than 100 pg/ml. Conclusion: In this study, most of the patients were anemic most probably due to low dose of EPO and inadequate dialysis. High turnover and mixed bone disorders were present in majority of the patients.